Analisis Faktor-Faktor yang Mempengaruhi Perilaku Pembelian Konsumen terhadap Produk Farmasi pada Platform E-Commerce: Tinjauan Sistematis - Rifai Arfan; Anna Wahyuni Widayanti; Suci Paramitasari Syahlani (Journal of Pharmaceutical and Sciences, 2026)
As digital technology advances, consumers increasingly purchase pharmaceutical products through e-commerce due to easier access, competitive prices and product variety. However, studies examining the determinants of online purchases of prescription and over-the-counter (OTC) medicines remain limited. This study seeks to determine the elements that influence customers' decisions to purchase pharmaceuticals through e-commerce platforms. A systematic review was performed utilizing databases including PubMed, Scopus, ScienceDirect, Google Scholar, and Garuda. This study is limited to publications from 2012 to 2025. The data were analyzed using the TDF and COM-B frameworks. Results showed that eleven overarching themes influence consumers' decisions to purchase medicines through e-commerce platforms. These themes include price and cost savings, medicine and service quality, data security and privacy, risks and limitations, accessibility and convenience, product availability, logistics and delivery services, insurance policies and integration, user experience, customer service, and social or habitual factors. Preliminary evidence suggests that price may be a more influential factor in studies conducted in Asian developing countries, whereas quality, data security, and regulatory considerations were more frequently reported in the limited number of studies from developed countries.